Édouard Glissant’s intellectual marronage into the world - Moses März (Francosphères)
This article studies Édouard Glissant’s personal political practice as an intellectual marronage into the world. A particular focus lies on the inherent community-creating dimension of this kind of marronage, which is conceptualized as a highly productive and complex political strategy geared towards fostering alternative forms of community. By discussing a map that traces the worldly direction of Glissant’s organizational commitments, along with their respective relevance to the constitution of smaller and larger ‘worldcommunities’, Glissant’s intellectual marronage is presented as being equally concerned with transformations on the plane of the imaginary and the invention of concrete institutional structures. In the context of debates on Glissant’s world thought, this article complements philosophic discussions of Glissant’s abstract conceptions of the world by exploring the concrete implications of his assertion that the world constituted the ultimate object of his poetic and political practice.